Chronic viral hepatitis and its association with liver cancer - Tu, Thomas; Bühler, Sandra; Bartenschlager, Ralf (Biological chemistry, 2017)
Chronic infection with hepatitis viruses represents the major causative factor for end-stage liver diseases, including liver cirrhosis and primary liver cancer (hepatocellular carcinoma, HCC). In this review, we highlight the current understanding of the molecular mechanisms that drive the hepatocarcinogenesis associated with chronic hepatitis virus infections. While chronic inflammation (associated with a persistent, but impaired anti-viral immune response) plays a major role in HCC initiation and progression, hepatitis viruses can also directly drive liver cancer. The mechanisms by which hepatitis viruses induce HCC include: hepatitis B virus DNA integration into the host cell genome; metabolic reprogramming by virus infection; induction of the cellular stress response pathway by viral gene products; and interference with tumour suppressors. Finally, we summarise the limitations of hepatitis virus-associated HCC model systems and the development of new techniques to circumvent these shortcomings.